Family Support in Perineal Wound Care for Postpartum Mothers in Lampung - Salsabilla, Salsabilla; Oktariza, Rury Tiara; Purwoko, Mitayani (Indonesian Journal of Medical Anthropology, 2025)
Cases of perineal wounds in postpartum mothers are still frequently encountered in Indonesia. One of the factors that can influence the healing of perineal wounds is the role of the family in the care of perineal wounds. This study aims to determine the role of the family in perineal wound care for postpartum mothers. The type of this research is qualitative with a phenomenological approach. Data were obtained through in-depth interviews with 5 informants who are family members (husbands) of postpartum mothers with perineal wounds in the working area of Puskesmas Rama Indra, Lampung. The data were triangulated with a midwife from Puskesmas Rama Indra, Lampung. The results of this study found that the types of family support for postpartum mothers with perineal wounds included instrumental, emotional, informational, and esteem support. Work schedules and local customs become obstacles in assisting the postpartum mother's care. It was found that there is a phenomenon of insufficient family involvement in the early mobilization of postpartum mothers and local customs that hinder perineal wound care. Conclusion, the role of the family still needs to be improved in terms of assisting early mobilization of postpartum mothers with perineal wounds.